2018
DOI: 10.1007/s11740-018-0805-4
|View full text |Cite
|
Sign up to set email alerts
|

Influence of processing parameters on quality factors of one-shot hybrid structures made by RTM

Abstract: This paper is dealing with the influence of processing parameters for manufacturing of steel-carbon-fiber-reinforced-plastic (CFRP) hybrid plates by using the one-shot-hybrid resin-transfer-moulding (OSH-RTM) process. A design of experiments study was carried out. The quality of the manufactured parts was quantified by the bending modulus, the apparent interlaminar shear strength (ILSS), the maximum deflection and the density of the CFRP. The following changeable processing parameters were chosen: mould temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
(33 reference statements)
0
6
0
Order By: Relevance
“…In the standard procedure, the interface between the two components is built in a separate gluing step, while in the novel approach, it is realized during the RTM process. This makes the procedure much more productionrelated for the one shot hybrid (OSH)-RTM process [4][5][6].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the standard procedure, the interface between the two components is built in a separate gluing step, while in the novel approach, it is realized during the RTM process. This makes the procedure much more productionrelated for the one shot hybrid (OSH)-RTM process [4][5][6].…”
Section: Methodsmentioning
confidence: 99%
“…As already shown in previous studies the difference in the thermal expansion coefficients of CFRP and steel leads to deformations of hybrid plates [5,28]. To reduce the resulting stresses and deformations, an uncoupling approach was used for this study.…”
Section: Hybrid Cfrp Steel Plate Manufacturingmentioning
confidence: 97%
See 1 more Smart Citation
“…For instance, knowing In from one simulation with reference injection conditions, the fill time tinj for generic time- In order to draw a complete moldability map, minimum and maximum values of each process parameter must be set. Those limit values are defined by the manufacturing set-up or other constraints [32]: for example, P min is the minimum injection pressure and P max is the maximum pressure reachable by the injection pump or is determined by the maximum allowed mold deflection; the limit temperatures T min and T max are set by the mold heating system or by the overall thermal stability requirements; the limit fill times t min and t max may be given by productivity constraints or by limitations due to viscosity or even be connected to fiber washing issues [31].…”
Section: Optimization Of Process Parametersmentioning
confidence: 99%
“…Recent research activities have shown, that the gluing step can be integrated into the impregnation stage of the resin transfer moulding (RTM) process [13][14][15]. There, the metal component is placed inside the mould at the same time as the textile preform.…”
Section: Introductionmentioning
confidence: 99%